INSOMNIA TREATMENT IN ADULTS OVER AGE 50 WITH OSTEOARTHRITIS PAIN: EFFECTS ON PHYSICAL FUNCTION AND QUALITY OF LIFE. (11th November 2018) - Heffner, K; France, C; Quinones, M; Pigeon, W
Abstract: Insomnia is prevalent among adults with osteoarthritis (OA), a common degenerative disorder for which age is a primary risk factor. Research suggests that cognitive-behavioral therapy for insomnia (CBTi) in older adults with comorbid chronic pain can improve sleep, with weaker effects on reported pain. In the current pilot study, we tested whether CBTi improved OA-related physical limitations and quality of life, as well as insomnia, as these factors are important contributors to well-being in aging. Thirty three adults, ages 51 to 74 years (Mean (SD) age=60.8(6.8)), with OA-related knee pain and insomnia were randomized to 6-session CBTi (n=16) or a weekly phone contact control group (n=17). The Insomnia Severity Index, WOMAC Osteoarthritis Index scales (pain, stiffness, and physical limitations), and WHO Quality of Life domain scales (physical health, psychological, social, environment) were assessed prior to randomization and 8-weeks later. General linear models indicated that participants in the CBTi group relative to the control group showed significantly larger declines over time in insomnia severity (p<.001), and larger improvements in OA-related symptoms based on total score on the WOMAC (p=.03), which was due to reductions in physical limitations (p=.01), but not pain (p=.47). WHO Quality of Life physical health (p=.001) and environment (p=.04) domain scores showed significantly larger improvements in the CBTi group compared to the control group. Age did not play a significant role in outcomes. CBTi is a promising approach to improve well-being and promote healthy aging among adults with comorbid osteoarthritis pain and insomnia.